Trends in child maltreatment in Germany: comparison of two representative population-based studies - Witt, Andreas (Child Adolesc Psychiatry Ment Health, 2018)
BACKGROUND: Child maltreatment of all types is a serious concern for society, and it is important to monitor trends in incidence in order to inform child welfare agencies and policy-makers about emerging issues. In Germany, however, information on such trends is limited: apart from official sources, the only published study is a comparison of surveys conducted in 1992 and 2011 that had focused primarily on sexual abuse. The present study is the first to look at more recent trends and to examine other types of maltreatment as well. METHODS: We compared the datasets of two population-based nationwide surveys, one conducted in 2010 (N = 2504) and the other in 2016 (N = 2510). Both had used identical methodology. Participants aged 14 years and older had been selected randomly using the Kish selection grid method, and information about childhood experiences of abuse had been solicited using the Childhood Trauma Questionnaire. RESULTS: The overall percentage of respondents who reported having experienced at least one type of child maltreatment decreased over the 6 years, from 35.3% in 2010 to 31.0% in 2016; however, the percentages who reported multiple types of maltreatment remained stable. The decrease in any type of maltreatment was mainly driven by fewer reports of physical neglect, which was likelier to be reported by older respondents who had experienced privation during the (post-) war years and whose representation was lower in the later survey. There was a significant increase over time in the prevalence of emotional abuse, with respondents aged 26–45 years reporting higher rates of this type of maltreatment. The prevalence rates of other types of maltreatment remained unchanged. All effect sizes were very small. CONCLUSIONS: At present, the systems in place in Germany for monitoring the occurrence of child maltreatment are insufficient. While this study contributes to a better understanding, more information is needed, particularly on populations that have been excluded or underrepresented in previous research efforts. As has been done elsewhere, large databases should be set up, using identical methodologies and definitions, in order to accurately assess trends over time in different types of abuse and neglect.